Green Repurchase Intention of Wiguna Market Visitors: The Role of Green Perceived Value, Green Perceived Quality, Green Wom With Green Trust As Mediation - Pranatasari, Fransisca Desiana; Diva VW, Maria Angela (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Now green marketing is one of the marketing strategies as a positive response to the situation of the earth and consumers who are starting to care about the environment. Green repurchase intention is one of the targets and objectives of green marketing. Increasing demand for environmentally friendly products is the focus of several researchers to contribute to providing the best marketing solutions for environmentally friendly products and the consumer segments that are their target markets. Pasar Wiguna is one of the communities in Yogyakarta that is committed to being a place for consumers to participate in protecting the earth from the aspect of sustainable product consumption, maintaining a supply chain that cares about the environment from the beginning to the end of the product. Therefore, research on green repurchase intention is very suitable for visitors to Pasar Wiguna. This study aims to analyze the role of green perceived value, green perceived quality, green WOM on green repurchase intention with green trust as a mediator. Data collection was carried out through a survey of buyers of environmentally friendly products or community visitors and/or visitors who had visited Pasar Wiguna Yogyakarta for the second time or more. The proposed hypothesis was completed with the PLS-SEM model through Smart-PLS1 software. The results are that Green Trust fully mediates the relationship between Green Perceived Value and Green Repurchase Intention; Green Trust fully mediates the relationship between Green Perceived Quality and Green Repurchase Intention; Green Trust does not mediate the relationship between Green WOM and Green Repurchase Intention.